헤더-채널 분기관의 채널 돌출길이가 2상 유동 분배에 미치는 영향에 대한 연구 - 이준경(Jun Koung Lee) (설비공학 논문집, 28(11), 2016)
The main objective of this work is to experimentally investigate the effect of angle variation and intrusion depth of channels on the distribution of two-phase flow at header-channel junctions. The dimensions of the header and the channels in cross-section were fixed at $16mm{×}16mm$ and $12mm{×}1.8mm$, respectively. Air and water were used as the test fluids. Two different header-channel positions were tested : a vertical header with horizontal channels (case VM-HC) and a horizontal header with horizontal channels (case HM-HC). In all cases, the intrusion depths of the channels are 0 mm, 2 mm, and 4 mm. For the case of the intrusion depth of VM-HC, the flow distribution became more uniform. However, the intrusion depth negatively affected the flow distribution for the case of HM-HC because liquid separation delay occurred.